Preparation and therapeutic evolution of Ficus benjamina solid lipid nanoparticles against alcohol abuse/antabuse induced hepatotoxicity and cardio-renal injury. Issue 57 (19th July 2017) - Sharma, Arun K.; Kumar, Ashish; Kumar, Shantanu; Mukherjee, Siddhartha; Nagpal, Dheeraj; Nagaich, Upendra; Rajput, Satyendra K.
Abstract : Chronic alcoholism destroys the propensity for hepatic detoxification of toxic substances, which further promotes the rapid and intense accumulation of aldehydes in the liver. Abstract : Chronic alcoholism destroys the propensity for hepatic detoxification of toxic substances, which further promotes the rapid and intense accumulation of aldehydes in the liver. Subsequently, chronic alcoholism exerts fatal liver and cardio-renal injury caused by fat deposition, dyslipidemia, inflammation and oxidative stress. The consequence becomes more perilous in disulfiram (potent aldehydes dehydrogenase inhibitor)-allied alcoholism, which further increases hepatic aldehyde accumulation by inhibiting aldehyde dehydrogenase. Ficus benjamina ( F. benjamina ) is rich in phenolic and total flavonoid content and demonstrates effective antioxidant, anti-inflammatory, antinociceptive, antipyretic, hypotensive, anti-dysentery and antimicrobial properties. Numerous formulations of Ficus benjamina solid lipid nanoparticles (FBSLNP) were prepared and characterized using several physicochemical and drug stability parameters including entrapment efficiency, particle size, zeta potential, and TEM and in vitro drug release studies. In vivo evaluation of FBSLNP was carried out against hepatic and cardio-renal injury induced by concurrent administration of alcohol and disulfiram. Imperative recoveries in studies involving biological parameters including SGPT/SGOT, alkaline phosphatase level, lipid profile, serum protein and oxidative stress, and histological photomicrography revealed the hepatoprotective action of FBSLNP. Reduced levels of accumulated aldehydes in liver tissue were observed via gas chromatography, which confirmed the detoxifying nature of FBSLNP. Moreover, the restoration of aberrant cardio-renal biomarkers (CKMB, LDH, cTnI and serum creatinine, blood urea nitrogen, and microproteinuria) and histological consequences significantly reveal the cardio-renal protective potential of FBSLNP against alcohol abuse/antabuse-associated injury. Considering the results, it may conclude that the significant protection by FBSLNP is based on its anti-oxidant, anti-inflammatory and detoxification potential with regard to accumulated hepatic aldehydes.